Developing an integrated RIASEC-QR code quartet game: a design and validation study for enhancing personality-based career understanding - Abdullah Sinring; M. Amirullah; Sarah Shafa Zahrani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
Students at MAN Kepulauan Selayar face serious challenges in making career decisions due to a lack of understanding of careers according to their personality types. This development research aims to produce RIASEC Quartet media as a career guidance to improve students' career orientation based on John Holland's personality theory. Using DDR with ADDIE (Analysis, Design, Develop, Implement, and Evaluate) design model, data were collected from 64 students using a validated IPKS questionnaire, needs analysis instruments, expert assessment instruments, and small group test instruments. The main product innovation lies in the integration of the traditional quartet card game with QR code technology, which serves as a gateway to a broader digital career information system on Google Sites. The results of the study showed that this media was